Impact of demand-side retrofit on the energy savings at the Universiti Teknologi Malaysia - Majid, M. S.; Taha, F. M.; Maricar, N. M.; Rahman, S. (2000)
This paper consists of a case study in retrofitting the library building at the Universiti Teknologi Malaysia primarily for demand side management applications involving lighting and air-conditioning systems. The data acquisition and monitoring system was installed in the early stages of the work. Its function was to monitor, record and store the measured data within the library. Lighting retrofit included replacing common magnetic ballasts with electronic ones, installing high quality reflectors and energy-saving 26-mm fluorescent tubes. This provided the opportunity for delamping from the original 3-tube fixture to a single tube. Air-handler retrofits included modifications to or replacements of the motors, fans, belts, and other relevant equipment, which reduced the energy usage of the system and improved the comfort level for the library patrons. The retrofit exercise generated savings of more than 300 kW of peak load, which is more than 39% of the total building load. More than 70% of these savings came from lighting retrofits. And with 378 hours of operation of the library per month, the payback was less than 2 years